STRATEGI LAYANAN BIMBINGAN KARIER UNTUK MENDUKUNG KEMATANGAN KARIER - Mhd. Taufik Hidayat; M. Fahli Zatrahadi; Miftahuddin (Counseling Milenial (CM), 2026)
Career maturity among high school students needs attention because students are at an important stage in determining further study plans and future career choices. Some students still experience difficulties in recognizing their interests, understanding educational opportunities, interpreting career information, and making responsible decisions. This article aims to examine career guidance service strategies to support high school students' career maturity. This study used a literature review method with a qualitative-descriptive approach. The reviewed literature consisted of national journal articles, academic books, and methodological references relevant to career guidance, career maturity, career planning, career exploration, digital media, self-concept, and guidance and counseling services. The findings show that career maturity can be supported through career information services, career exploration, classical guidance, group guidance, digital media utilization, self-concept strengthening, and collaboration between school counselors and the school environment. These strategies help students understand their potential, evaluate alternative choices, and develop more realistic career plans. This review emphasizes that career guidance should be designed systematically, contextually, and continuously.